2019
DOI: 10.3133/ofr20191006
|View full text |Cite
|
Sign up to set email alerts
|

Assessing causes of mortality for endangered juvenile Lost River suckers (Deltistes luxatus) in mesocosms in Upper Klamath Lake, south-central Oregon, 2016

Abstract: For more information on the USGS-the Federal source for science about the Earth, its natural and living resources, natural hazards, and the environment-visit http://www.usgs.gov/ or call 1-888-ASK-USGS (1-888-275-8747).For an overview of USGS information products, including maps, imagery, and publications, visit

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 31 publications
2
22
1
Order By: Relevance
“…Finally, we examined the hypothesis that the range in psat is correlated with the hazard rate (PsatRange model; Hereford et al. ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we examined the hypothesis that the range in psat is correlated with the hazard rate (PsatRange model; Hereford et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to a previous mesocosm study that lacked comparable water quality data among mesocosm sites (Hereford et al. ), the design of the current study facilitated application of hazard models to test hypotheses about short‐term and chronic effects of single and co‐occurring water quality parameters on fish survival.…”
mentioning
confidence: 99%
“…The presence of Ichthyobodo spp. on wild juvenile Lost River Suckers in the lake has been documented (Burdick et al 2017), and ichthyobodiasis was the identified cause of morbidity for several juvenile Lost River Suckers held in mesocosms in the lake (Hereford et al 2019). Because wild fish are less likely to experience fish‐to‐fish contact, the risk of Ichthyobodo spp.…”
Section: Discussionmentioning
confidence: 99%
“…Ichthyobodo is a genus of dinoflagellate protozoans of the skin and gills. Usually, in low numbers, they do not cause clinical signs, or significant mortalities (Martins et al, 2015;Hereford et al, 2019). They have more importance to alevins, juvenile fishes, and even to eggs.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, Ichthyobodo infection is associated with immunosuppression and stress. Higher temperatures accelerate their reproduction; thus, heat stress contributes to both stress and debility, and more Ichthyobodo in water (Woo, 2006;Hereford et al, 2019). There are reports of O. niloticus being more resistant to these ectoparasites and only being infected in the caudal region (Woo, 2006).…”
Section: Discussionmentioning
confidence: 99%